A new model of batch biodrying of sewage sludge, Part 1: Model development and simulations. Issue 6 (26th April 2017) - Huiliñir, César; Pérez, Juan; Olivares, Daniel
ABSTRACT: This study proposes a new model of batch biodrying of sewage sludge. This model divided the matrix into two phases (gas and solid), generating 9 · N equations which were solved numerically with Matlab software. A sensitivity analysis was also performed. It was found that the model can represent the experimental trend reported in the literature for the biodrying process, such as higher temperatures ( T ) for higher initial moisture content (MC) and higher T differences at lower initial MC. The sensitivity analysis shows that the model is mainly affected by changes in parameters k h, rb, k h, sb, µ max, UA, d p, X sb, 0, and X H, 0 .